Prognostic impact of tumor size on cancer-specific survival for postoperative WHO grade II oligodendroglioma: a SEER-based study - Qin Lu; Yongyan Wu; Yonglin Xie; Shuxu Yang; Hongchuan Jin (Frontiers in Surgery)
BackgroundWHO grade II oligodendroglioma (OG/II) is a rare primary brain tumor with various outcomes. Our study aims to investigate prognostic factors for postoperative OG/II patients and then evaluate the instructional value of tumor size.MethodsWe retrospectively studied the cases from the Surveillance, Epidemiology, and End Results (SEER) database. Univariate and multivariate Cox analyses and Kaplan-Meier survival curves were used to identify and assess prognostic factors. The optimal cut-off value of tumor size was determined by X-tile analysis and verified by multivariate analyses. Subsequently, Subgroup analyses were performed based on tumor size.Result676 OG/II patients were enrolled in our study. Multivariate Cox analyses revealed that age > 60 (HR 3.52), male (HR 1.48), total resection (HR 0.38), and tumor size (HR 2.04) were independent factors in predicting cancer-specific survival (CCS). The optimal cut-off value for tumor size was 60 mm. Patients with tumor size less than 60 mm, age > 60 (HR 3.82), and radiation (HR 1.58) were associated with worse CSS, while total resection (HR 0.35) was associated with better CSS. Lastly, a tumor size-based nomogram was established objectively and accurately.ConclusionOur study identified four crucial prognostic factors related to CSS in postoperative OG/II patients: age, sex, the extent of recession, and tumor size. A tumor size of 60 mm was an optimal cut-off point for dividing patients into low and high-risk groups. Patients in the low-risk group may not benefit from extended resection and radiation. Tumor size can be a valuable factor for making therapeutic schedules.